Designing online movie ticket reservation module / Normazni Ujang - Ujang, Normazni (2010)
Nowadays, online movie ticket reservation is widely used by people who are alert with existing technologies in our life. Most of the current system use general input device such as keyboard and mouse to enter the data. This study provides another alternative for user who uses Internet to reserve or book the movie ticket by using their voice as the input method. Speech-to-text technique that is available in Windows Vista will be used to design this alternative method based on the proposed objectives of this study. As the result, the people with disabilities and Carpal Tunnel Syndrome can take advantage from this reservation technique.